2001
DOI: 10.1192/apt.7.4.283
|View full text |Cite
|
Sign up to set email alerts
|

African–Caribbeans and schizophrenia: contributing factors

Abstract: Dinesh Bhugra is a reader in cultural psychiatry and heads the Section of Cultural Psychiatry at the Institute of Psychiatry (De Crespigny Park, Denmark Hill, London SE5 8AF). His research interests include cultural factors and social psychiatry, sexual dysfunction and sexual deviation. Kamaldeep Bhui is a senior lecturer in the Department of Psychiatry at St Bartholomew's and the Royal London School of Medicine, London. He is interested in cultural psychiatry and his research interests include working with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…[54] Often, culturefocused researchers have found that this process led to frequent misdiagnoses. [7] This is particularly evident if considering the body of knowledge signifying, for example, that auditory hallucinations are dependent on the pathoplastic influences of culture. [7] The manifestation of pathology across cultures is diverse.…”
Section: Articlementioning
confidence: 99%
See 3 more Smart Citations
“…[54] Often, culturefocused researchers have found that this process led to frequent misdiagnoses. [7] This is particularly evident if considering the body of knowledge signifying, for example, that auditory hallucinations are dependent on the pathoplastic influences of culture. [7] The manifestation of pathology across cultures is diverse.…”
Section: Articlementioning
confidence: 99%
“…[7] This is particularly evident if considering the body of knowledge signifying, for example, that auditory hallucinations are dependent on the pathoplastic influences of culture. [7] The manifestation of pathology across cultures is diverse. [17] Symptoms, therefore, ought to be largely interpreted within the cultural context.…”
Section: Articlementioning
confidence: 99%
See 2 more Smart Citations
“…There are ongoing debates about the shortfalls in present-day psychiatric services when dealing with ethnic minority cultures, and fears about such ethnic minority patients being over-diagnosed with psychotic illnesses due to a lack of awareness of cultural norms (Bailey et al, 2004;Bhugra and Bhui, 2001). There was, however, no significant difference found between ethnic groups in terms of psychiatric diagnosis in this study.…”
Section: Ethnicitymentioning
confidence: 99%